Flexion Angles of Finger Joints in Two-Finger Tip Pinching Using 3D Bone Models Constructed from X-Ray Computed Tomography (CT) Images. (10th September 2020) - Shimawaki, Satoshi; Nakamura, Yoshiaki; Nakabayashi, Masataka; Sugimoto, Hideharu
Abstract : The motion analysis of two-finger tip pinching using the thumb and index finger provides crucial data for designing the motion mechanism of electric prosthetic hands. The purpose of this study is to determine the joints that have high mobility during two-finger tip pinching by measuring the flexion angle of each joint. Ten Japanese men with normal hand were selected. CT images were obtained while the hands adopted the following four postures: a basic posture not pinching a cylinder, and three postures pinching wooden cylinders with different diameters (2, 10, and 30 mm). Three-dimensional bone models of the thumb and index finger were created using the CT images and used to measure the flexion angles of the joints. The flexion angles of the proximal interphalangeal and metacarpophalangeal joints of the index finger significantly decreased as the diameter of the cylinder increased. However, even when the diameter of the cylinder changed, the flexion angle of the distal interphalangeal joint of the index finger, and the flexion and rotation angles of all of the thumb joints did not change. When pinching objects of different sizes with a two-finger tip pinch, the posture of the thumb is fixed, and only the posture of the index finger changes. When designing the two-finger tip pinch motion for an electric prosthetic hand, it is sufficient to drive the joints of the index finger only.